Computational fluid dynamic (CFD) and computational heat transfer (CHT) of stenosed artery - Wong, Zi Jing (2018)
Cardiovascular disease is the leading cause of death in current society. Root cause for having cardiovascular disease is mainly due to Atherosclerosis. Atherosclerosis generally no symptoms. It is a condition when the plaque formed in the artery walls, cause the blockage of the blood flow, limit the supply of oxygen and eventually lead to catastrophic problems, including stroke, heart attack or even death. Multiple test such as blood test, computed tomography (CT) scan, cardiac stress test and ultrasound scan are introduced to detect severe narrowed artery. However, all these diagnoses are still not sufficient. More techniques need to be explored for early detection of cardiovascular disease, especially non-contact technique. This study contributes to the development of Computational Fluid Dynamics (CFD) model of blood flow through the human vascular system. A 3-D model of artery with fats, dermis and skin is built to simulate the actual blood flow in human body. Temperature on skin surfaces are monitored and investigated. The results showed that there is big difference in skin temperature change for stenosed artery compared to non-stenosed artery. By applying cooling effect on human skin, the temperature difference for both nonstenosed and stenosed artery can be highly differentiated. Two types of cooling are discussed in this study which is continuous cooling and intermittent cooling. Both cooling methods are carried out in different cycles combination in random. After comparison, the best preferred cooling method is intermittent cooling 5-5 cycle at 273K.